Seismogenic structures and spatiotemporal seismicity patterns of the 2022 Ms6.0 Maerkang earthquake sequence, Sichuan, China - Feng, Long; Chang, He; Guixi, Yi; Xiaohui, He; Li, Li; Fuqiang, Shi; Yue, Gong; Liyuan, Peng (Frontiers in Earth Science, 2023)
The 2022 Ms6.0 Maerkang earthquake sequence, Sichuan, China, occurred in an unexpected area with historically rare seismicity in the Bayan Har block. Here we relocated the earthquake sequence, inverted for the focal mechanisms of the larger events, and calculated the rupture directivity of the earthquake sequence to reveal the seismogenic structures and mechanisms of this sequence. The high-precision relocations indicate that the seismogenic structures consist of several clusters that are generally parallel to the nearby NW-trending Songgang fault, and relatively small-scale conjugate faults are also identified. The seismicity migrated from cluster 1 in the south to cluster 2 in the north during the sequence. Furthermore, the hypocenters were largely located at 5–10 km depth, thereby highlighting that the seismogenic structures are buried. The vertical fault planes of the seismogenic structures are consistent with the high-dip focal mechanism solutions from seven events. A stress field inversion based on the focal mechanisms indicates that the sequence occurred in a strike-slip environment that was controlled by a NNW–SSE-striking principal compressive stress. The different rupture directivities of the Ms5.8 (southwestward) and Ms6.0 (southeastward) events prove the existence of conjugate faults. The Ms5.8 event induced a coseismic Coulomb stress change of 1.6 MPa where the Ms6.0 event subsequently occurred, thereby highlighting that the Ms5.8 event triggered the Ms6.0 event and produced the spatiotemporal seismicity pattern of the sequence. We therefore conclude that the seismogenic structures of the 2022 Ms6.0 Maerkang earthquake sequence are previously unknown concealed conjugate structures associated with the main Songgang fault. The complex seismogenic structures and their potential to generate large earthquakes warrant the need to better understand the seismogenesis of this area and the seismic risks that may be present.